SOME INFORMATION ABOUT THE HISTORY OF THE FERGHANA ETHNIC SCHOOL (Scientific journal of the Fergana State University, 2026)
The article provides some scientific observations on the Namangan school of epic poetry. As a result of the analysis of the research, new information was provided about the Pop school of epic poetry, which is part of this school, and the activities of its representative Madrahim Bakhshi Boltaboev. It was also concluded that new research should be conducted in this regard and scientific publications should be presented. This indicates the need to study oral and archival materials, samples of epic poetry stored in scientific research institutes and museum funds.